RESPONSIBILITY OF BUSINESS ACTIVITIES IN ELECTRONIC TRANSACTIONS THROUGH THE INTERNET SITE VIEWING FROM THE LEGAL PERSPECTIVE OF CONSUMER PROTECTION - Dwi Atmoko (HERMENEUTIKA : Jurnal Ilmu Hukum, 2022)
At first the internet network could only be used by the educational environment (colleges) and research institutions. Then in 1995, the new internet can be used for the public. With the application can make it easier for people to access information on the internet. After the opening of the internet for the public interest, more and more business applications have sprung up on the internet. Users of electronic systems, also known as consumers, can quickly find out about information developments in various parts of the world. By relying solely on search engines such as Google and Yahoo, electronic system users around the world have easy internet access to various kinds of information. Compared to books and libraries, the internet symbolizes the spread (decentralization), knowledge (knowledge) of information and data to the extreme. The internet can also be used by the government in providing public services. The internet is the easiest means to meet the needs of finding information that consumers want.